An Equilibrium Analysis of Marriage, Divorce and Risk-Sharing - Dan Anderberg (Center for Economic Studies and ifo Institute (CESifo), 2001)
This paper considers family formation and reciprocity-based cooperation in the form of sharing of earnings-risk. While risk sharing is one benefit to marriage it is also limited by divorce risk. With search in the marriage market there may be multiple equilibria diering not only in divorce rates but also in the role of marriage in providing informal insurance. Publicly provided insurance, despite potential equilibrium multiplicity, is shown to aect family formation and financial cooperation monotonically. Some aspects of the model are then tested using international survey data and a bivariate probit model with sample selection.
Keywords: 330; Marriage; divorce; risk-sharing